Landscape management for disaster-prone cities: disaster resilient park proposal - Ömer Faruk Başgün; Yahya Bulut (Journal of Environmental Engineering and Landscape Management)
Elazığ is a disaster-prone city due to its geological structure, proximity to fault lines, and similar reasons. As part of the study, a disaster-resilient green space model applicable to the city has been developed. The study examines how green spaces should be planned and designed to be used in disaster situations. The methodology of the study consists of three phases. (1) The city of Elazığ was analyzed in terms of disasters. (2) UAV and GPS CORS devices were used to collect data in the area designated as the disaster park and three-dimensional spatial analysis was performed. (3) The disaster park was designed according to the data obtained. The results show that Elazığ is frequently affected by disasters. Therefore, it is understood that the city needs a disaster-resistant green system. Suggestions for the design of disaster parks and their inclusion in the landscape management of disaster-prone cities have been developed.